Analisis Kritis Tentang Konsep Misi Kaum Postmodernis Dalam Perspektif Teologi Reformed - Agustina Pasang; Triana Tambunan; Febriaman Lalaziduhu Harefa (JURNAL LUXNOS, 2023)
Abstract: The aim of this research is to critically analyze the postmodernist concept of mission from a Reformed perspective. This is motivated by the phenomenon of shifting culture and thinking of modern society towards the postmodern era. This change has an impact on the perspective of Christian mission which has an impact on the church in developing its duties to carry out the great commission. The approach used is qualitative with library research methods. Research results and analysis. First, the basic mission of the postmodernists does not depart from Bible revelations, resulting in a fictional concept of mission that does not reflect the reality of the truth itself. Second, the focus of the postmodernist mission is oriented towards liberating humans from social issues and setting aside the proclamation and finality of Jesus Christ as the center of Christian mission. Third, the postmodernist mission approach only emphasizes theological dialogue, so it does not present a complete and holistic truth value. The postmodernist emphasis on one mission approach results in an imbalance in the implementation of mission applications. The conclusion of this study shows that the postmodernist concept of mission in the Reformed perspective has several weaknesses and inconsistencies in terms of biblical basis, mission focus, and mission approach. This raises inequality in the application of the mission concept. There needs to be a critical evaluation and understanding of the postmodernist concept of mission, so that the church can develop its duties in carrying out the great commission in accordance with biblical principles. Abstrak:       Tujuan penelitian adalah menganalisis secara kritis konsep misi kaum postmodernis dalam perspektif Reformed. Hal ini dilatarbelakangi oleh fenomena pergeseran budaya dan pemikiran masyarakat modern menuju era postmodern. Perubahan ini berdampak pada cara pandang terhadap misi Kristen yang berdampak kepada gereja dalam mengembangkan tugasnya untuk melaksanakan amanat agung. Pendekatan yang digunakan adalah kualitatif dengan metode penelitian kepustakaan. Hasil penelitian, pertama, dasar misi kaum postmodernis bukan bertolak dari penyataan Alkitab sehingga menghasilkan konsep misi yang fiksi dan tidak mencerminkan sebuah realitas dari kebenaran itu sendiri. Kedua, fokus misi kaum postmodernis berorientasi pada pembebasan manusia dari isu sosial serta mengesampingkan proklamasi dan finalitas Yesus Kristus sebagai pusat misi Kristen. Ketiga, pendekatan misi kaum postmodernis hanya menekankan pada dialog teologis, sehingga tidak menghadirkan nilai kebenaran yang utuh dan holistik. Penekanan kaum postmodernis terhadap salah satu pendekatan misi membutikan ketimpangan dalam pelaksanaan aplikasi misi. Kesimpulan penelitian ini menunjukkan bahwa konsep misi kaum postmodernis dalam perspektif Reformed memiliki beberapa kelemahan dan ketidakkonsistenan dalam hal dasar Alkitab, fokus misi, dan pendekatan misi. Hal ini memunculkan ketimpangan dalam penerapan konsep misi tersebut. Perlu adanya evaluasi dan pemahaman yang kritis terhadap konsep misi kaum postmodernis, sehingga gereja dapat mengembangkan tugasnya dalam melaksanakan amanat agung sesuai dengan prinsip Alkitab.